A simulation method for analyzing the effect of external forces on the optical performance of liquid crystal displays. (22nd September 2019) - Gong, Xin; Lv, Guo-qiang; Li, Jun-jun; Hu, Zi-ang; Wang, Zi; Feng, Qi-bin
Abstract: A simulation method is proposed to analyze the effect of external forces on the optical performance of LCDs. The method consists of three steps: in the first step, the structure deformation of substrates under the influence of external forces is simulated. Secondly, the variations of electrode thickness are used to represent the structure deformation. Then, the force–optical performance of the LCD can be achieved. An experiment is performed to verify the proposed method. Besides, the LC director distribution and optical performance changes are discussed. The method can help predict the change in optical performance of LCDs in harsh environments.